“Anatomy and Imaging”: 10 Years of Experience with an Interdisciplinary Teaching Project in Preclinical Medical Education – From an Elective to a Curricular Course - Schober, A.; Pieper, C. C.; Schmidt, R.; Wittkowski, W. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: Presentation of an interdisciplinary, interactive, tutor-based preclinical teaching project called “Anatomy and Imaging”.Materials and Methods: Experience report, analysis of evaluation results and selective literature review.Results: From 2001 to 2012, 618 students took the basic course (4 periods per week throughout the semester) and 316 took the advanced course (2 periods per week). We reviewed 557 (return rate 90.1 %) and 292 (92.4 %) completed evaluation forms of the basic and the advanced course. Results showed overall high satisfaction with the courses (1.33 and 1.56, respectively, on a 5-point Likert scale). The recognizability of the relevance of the course content for medical training, the promotion of the interest in medicine and the quality of the student tutors were evaluated especially positively.Conclusion: The “Anatomy and Imaging” teaching project is a successful concept for integrating medical imaging into the preclinical stage of medical education. The course was offered as part of the curriculum in 2013 for the first time. “Anatomia in mortuis” and “Anatomia in vivo” are not regarded as rivaling entities in the delivery of knowledge, but as complementary methods.Key points:• “Anatomy and Imaging” is an interdisciplinary, interactive, tutor-based preclinical teaching project.Imaging techniques potentially deliver anatomical knowledge effectively.• Student tutors enable teaching in small groups (up to 10 participants).• Since 2013, the former elective has become part of the curriculum.• The course introduces preclinical students to radiology.Citation Format:• Schober A, Pieper CC, Schmidt R et al. “Anatomy and Imaging”: 10 Years of Experience with an Interdisciplinary Teaching Project in Preclinical Medical Education – From an Elective to a Curricular Course. Fortschr Röntgenstr 2014; 186: 458 – 465
Keywords: education; anatomy; teaching of anatomy; radiologic anatomy; preclinical curriculum